2004
DOI: 10.1081/ncn-200027718
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of 5‐Fluorouracil with UCN‐01 or Staurosporine

Abstract: The action of 5-Fluorouracil (5-FU) is mediated by inhibition of thymidylate synthase (TS), which is regulated by cell cycle proteins controlled by protein phosphorylation. We studied the effects of staurosporine and its analogue UCN-01, inhibitors of protein kinase C (PKC) on 5-FU cytotoxicity in Lovo colon cancer cells. Each drug contributes equally to the cell cycle effects of the 5-FU combinations. In sequential drug administration, the cell cycle distribution was determined by the first drug. Simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Shao et al (2004) have previously shown that cytotoxicity was enhanced in human colon carcinoma HT‐29 cells when UCN‐01 was added after treatment with ara‐C. For 5‐fluorouracil we also showed a sequence‐dependent interaction in colon cancer cell lines (Sigmond et al , 2004).…”
Section: Drug Interaction Between Ara‐c and Six Potential Modulators supporting
confidence: 55%
See 1 more Smart Citation
“…Shao et al (2004) have previously shown that cytotoxicity was enhanced in human colon carcinoma HT‐29 cells when UCN‐01 was added after treatment with ara‐C. For 5‐fluorouracil we also showed a sequence‐dependent interaction in colon cancer cell lines (Sigmond et al , 2004).…”
Section: Drug Interaction Between Ara‐c and Six Potential Modulators supporting
confidence: 55%
“…Furthermore, it is able to abrogate checkpoints induced by genotoxic stress due to modulation in chk1 kinase (Senderowicz, 2001). Shao et al (2004) have previously shown that cytotoxicity was enhanced in human colon carcinoma HT-29 cells when UCN-01 was added after treatment with ara-C. For 5-fluorouracil we also showed a sequence-dependent interaction in colon cancer cell lines (Sigmond et al, 2004).…”
supporting
confidence: 62%
“…In mut-p53 cells this regulation is abrogated, so that UCN-01 by inhibition of the G2/M checkpoint regulators, will increase DNA damage. Moreover UCN-01 will further prevent DNA repair and enhance the effect of deoxynucleoside analogues ara-C, dFdC, 5-FU [26][27][28][29][30][31], the purine analogue fludarabine [26,32] and DNA binding agents such as cisplatin, thiotepa, mitomycin C, cisplatin, melphalan and topotecan [26]. Treatment with a DNA damaging drug (cisplatin, 5FU, nucleoside analogs or radiation) prior to UCN-01 or a novel ChK1 inhibitor (SCH00766) was synergistic and induced more cell death than vice versa through abrogation of the G2/M checkpoint and was associated by reduced expression of cyclins A and B and activation of Cdk1 [33,34].…”
Section: Discussionmentioning
confidence: 99%